2009
DOI: 10.3177/jnsv.55.317
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dietary Supplements among Preschool Children in Japan

Abstract: Summary This study was conducted to examine the characteristics and use of dietary supplements by preschool children in Japan. A survey was conducted among 2,125 parents of preschool children to discover the status of dietary supplement use and their attitudes towards supplement use by their children. Logistic regression models were used to determine which characteristics predict supplement use in this population. For detailed characterization, child supplement users were also categorized as either the users o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
3
27
1
Order By: Relevance
“…Mothers who used supplements during pregnancy were more likely to provide their infants with supplements than mothers who did not. This observation confirmed previous reports from the United States (13) and Japan (14), indicating the effect of parental history on the use of supplements.…”
Section: Discussionsupporting
confidence: 93%
“…Mothers who used supplements during pregnancy were more likely to provide their infants with supplements than mothers who did not. This observation confirmed previous reports from the United States (13) and Japan (14), indicating the effect of parental history on the use of supplements.…”
Section: Discussionsupporting
confidence: 93%
“…The utilization ratios of dietary supplements among Japanese children were reported to be between 7% and 15% in previous studies (10,(14)(15)(16); similar to those reports, the present study showed that 8% of children used dietary supplements.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study suggested that about 10% of Japanese preschool children used dietary supplements and that the factors contributing to supplement use among children were high prevalence of supplement use and high eating awareness among their parents (10). This previous study focused on the parents' awareness of supplement use; however, mothers' education levels, income levels, circumstances and attitudes towards eating habits were not addressed.…”
mentioning
confidence: 98%
“…The prevalence of dietary supplements, which are helpful to supply nutrients for health, has increased in Japan [1–3]. Consumers use not only vitamins and minerals, but also various other ingredients as dietary supplements.…”
Section: Introductionmentioning
confidence: 99%